Delayed Cutaneous Microvascular Responses With Non-consecutive 3 Days of Remote Ischemic Preconditioning - Kim, Jahyun; Franke, Warren D.; Lang, James A. (Frontiers in Physiology, 2022)
The optimal frequency and duration of remote ischemic preconditioning (RIPC) that augments microvascular function is unknown. A single bout of RIPC increases cutaneous endothelial function for ~48 hours, whereas one week of daily RIPC bouts results in more sustained endothelium-independent improvements. We hypothesized that 3 days of RIPC, separated by rest days (3QOD), will result in sustained increases in both endothelium-dependent and endothelium-independent function. Cutaneous microvascular function was assessed in 13 healthy young participants (age=20.5 ± 3.9 years; 5 male, 8 female) before 3QOD and then 24hr, 48hr, 72hr and a week after 3QOD. RIPC consisted of 4 repetitions of 5 minutes blood flow occlusion separated by 5 minutes reperfusion. Skin blood flow responses to local heating (Tloc=42oC), acetylcholine (Ach), and sodium nitroprusside (SNP) were measured by laser speckle contrast imaging and expressed as cutaneous vascular conductance (CVC=PU∙mmHg-1). Local heating-mediated vasodilation was higher 72 hr after 3QOD and the increased responsivity persisted a week later (1.08 ± 0.24 vs. 1.34 ± 0.46, 1.21 ± 0.36 PU∙mmHg-1; ΔCVC, pre- vs. 72 hrs, a week after 3QOD; P=0.054). Ach-induced cutaneous vasodilation increased a week after 3 QOD (0.73 ± 0.41 vs. 0.95 ± 0.49 PU∙mmHg-1; ΔCVC, pre- vs. a week after 3QOD; P<0.05). SNP-induced cutaneous vasodilation increased 24 hours after 3QOD (0.47 ± 0.28 vs. 0.63 ± 0.35 PU∙mmHg-1; ΔCVC, pre- vs. 24 hrs; P<0.05) but this change did not persist thereafter. Thus, 3QOD elicited sustained improvement in endothelial dependent vasodilation but was not sufficient to sustain increases in endothelial independent vasodilation.